National saving and fiscal policy in South Africa: an empirical analysis - Bonga-Bonga, Lumengo (Acta Academica: Critical views on society, culture and politics, 2009)
This article studies the dynamics of gross national saving, government saving and private saving in response to fiscal shocks, by using the impulse response functions (IRF) obtained from the structural vector autoregressive (SVAR). This article aims to determine the extent to which fiscal policy influences savings in South Africa, and to test whether the Ricardian equivalence proposition holds in South Africa. It concludes that the full Ricardian equivalence does not hold in the short term, and in the long term the response of national saving to fiscal policy shocks is neutral.